PERILAKU SOSIAL BUDAYA PENGIKUT TAREKAT DALAILUL KHAIRAT PADA PONDOK PESANTREN DARUL FALAH JEKULO KUDUS - MASTURIN, MASTURIN (LPPM IAIN Parepare, 2015)
Tarekat Dalailul Khairat is a congregation that is run by fasting for three years without stopping (except intime of fasting is forbidden according to Islamic law), and everyday reading the book of Dalailul Khairat (not boundby a specifc time), how to run it is not bound by place (ribat), and are not guided directly by the Sheikh (teacher). Al-Qur’an sees that religion and culture are different and must be clearly distinguished, butnot separated. Thus, Islam (The Qur’an) became into dialogue with space and time. Universal religion it will always fnd its relevance to specifc and concrete demands of its adherents, according to space and time, along with the dynamics and vitality. In doing Dalailul Khairat with good Behavior for three years, it becomes a habit of good behavior, that are somewhat forced, then the habith as become a kind of law, means the Congregation Dalailul Khairat positively infuences positive social behavior. Social behaviors are manifested by Dalailul Khairat followers such as diligent, patient, qana’a, tasamuh, constancy, obey the rules, honest, and hard work